CHARACTERISTICS OF DEVELOPMENT AND OF THE INFLUENCE OF TOURISM ON THE ENTIRE ECONOMY OF VOJVODINA - Gajić, Tamara (Economics of Agriculture, 2009)
The development of tourism and hotel industry puts into motion other complementary activities. In the general view, the region of Vojvodina was never characterized by mass tourism even though it was the branch of economy which could help in solving many economic problems – mostly unemployment. It is known that the amount of tourist visits to Vojvodina is not proportional to its anthropogenic and natural treasures. This paper points out the main characteristics about tourism development in Vojvodina region and influences it could exercise on certain branches and segments of economy. Inter-sector analyses show that within the most important segments (manufacturing and production, export, employment) tourist activities represents one of the most propulsive sectors of economy. The beneficial influence of this segment is confirmed in regional development. Tourist economy, definitely should be one of the strongest factors of economic stabilization, and also as a factor which removes disproportions made by negative movements of productivity and employment, raised on the base of unbalanced sector and regional process.